ROTATING SAVINGS AND CREDIT ASSOCIATION (ARISAN): IMPACT STUDY ON HOUSEHOLD-LEVEL ANALYSIS - Riska Dwi Astuti (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
Despite the fact that informal financial service is one of the most important alternative solutions for those in need yet do not have the capability to access the formal ones, its role is understudied. This study aims to analyze the impact of one of the informal financial services that have been developing within communities, rotating savings and credit association that is popular in term of arisan in Indonesia, on household economy measured by its spending on food and non-food. Using information from two latest data of Indonesian Family Life Survey processed with the difference in differences and matching methods, results show that household participation in the arisan is able to increase food and non-food expenditure after adjusted with inflation. Robustness checking through controlling several covariates shows consistent output sign and significances. It demonstrates that, statistically, arisan is able to improve its participant economic capabilities.